Pengendalian Hayati Penyakit Akar Merah pada Akasia dengan Trichoderma - S. M. Widyastuti; Sumardi Sumardi; A. Sulthoni; Harjono Harjono (Jurnal Perlindungan Tanaman Indonesia, 1998)
The experiment was aimed to measure the distribution and intensity of root rot disease of Acacia spp. in the urban forest at the campus of Gadjah Mada University, to isolate and identify the causal organism and to select Trichoderma sp. as biological agent for controlling the disease. The pathogenicity of the causal organism was tested using Crotalaria juncea L. and trunk of A. mangium Willd. (10 cm diameter, 8 cm length) as indicator plant. The ability of Trichoderma sp. as antagonist was tested in vitro. It was concluded that the pathogen of the root rot disease was Ganoderma philippii. The pathogen attacked for species of Acacia spp. in the location namely A. auriculiformis, A. mangium, A. oraria, and A. crassicarpa. Of the total individual trees of those species in the campus, as much as 38.6%, 22.2%, and 66.7% were attacked by the root rot pathogen respectively. Of the 20 Trichoderma spp. isolate capable to inhibit the pathogen in vitro, three isolates were found as promising agents for biological control of the pathogen. The promising isolates were T. resei/T23, T. koningii/T1, and T. koningii/T16 with inhibition effectivity of 94.58%; 93.66%; and 91.76% respectively.